UK guidelines for the medical and laboratory procurement and use of sperm, oocyte and embryo donors (2019). (1st January 2021) - Clarke, Helen; Harrison, Shona; Perez, Marta Jansa; Kirkman-Brown, Jackson
Abstract: This article updates the 2008 UK guidelines for the medical and laboratory screening of sperm, egg and embryo donors. This was achieved by a working group composed of representatives from: the Association of Biomedical Andrologists, the Association of Clinical Embryologists, the British Andrology Society and the British Fertility Society, with subsequent review and commentary from their respective memberships. Information and guidance on core facts which should be made evident to all parties involved in donation are provided. Changes with regard to transmissible disease screening include: (i) extended guidance regarding history taking, risk factors and deferral periods; (ii) recommended quarantine period for donors screened by Nucleic Acid Testing (NAT) and serology is now 3 months; (iii) recommended quarantine period for donors screened by serology alone is legally required to be 6 months; (iv) if donor oocytes, or embryos created with donor oocytes, are cryopreserved then the quarantine period should be observed as best practice. We further recommend that consideration be given to HPV vaccination of women who outside of insemination may not be exposed to HPV. For heritable diseases, the discussion and assessment of genetic risk have been fundamentally reviewed in light of technological advances. After review of scientific evidence, it has also been deemed acceptable for men to donate sperm up to their 46th birthday.